MANAJEMEN PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN HASIL BELAJAR IPAS DI SEKOLAH DASAR - Nurhayati; Siti Maryam Mansuryah; Dinny Mardiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the low level of student engagement and suboptimal learning outcomes in the subject of Integrated Natural and Social Sciences (IPAS). The aim of the research is to describe and analyze the implementation of management in interactive learning to improve IPAS learning outcomes among Grade V elementary school students. A qualitative approach with a case study method was used. Data collection techniques included in-depth interviews, classroom observations, and document analysis. The research subjects consisted of school principals, Grade V teachers, and students from two public elementary schools in Cianjur Regency. The data analysis process followed the Miles and Huberman model, involving data reduction, coding, categorization, data presentation, and conclusion drawing. The research findings indicate that effective interactive learning management involves three main components: (1) lesson planning focused on students’ learning needs; (2) lesson implementation that promotes active interaction between teachers and students through the use of various media and methods; and (3) evaluation that emphasizes formative feedback and reflection. The application of interactive learning management has been shown to positively contribute to increased student motivation and improved IPAS learning outcomes. This study provides both theoretical and practical contributions to the development of instructional strategies in elementary schools and emphasizes the importance of learning management as a foundation for creating meaningful, student-centered education.